Increased risk of mycotic infections associated with sodium–glucose co‐transporter 2 inhibitors: a prescription sequence symmetry analysis. Issue 1 (8th November 2018) - Adimadhyam, Sruthi; Schumock, Glen T.; Calip, Gregory S.; Smith Marsh, Daphne E.; Layden, Brian T.; Lee, Todd A.
Abstract : Aims: To determine the risk of mycotic infections associated with the use of sodium–glucose co‐transporter 2 inhibitors (SGLT2i) in a real‐world setting. Methods: We conducted a prescription sequence symmetry analysis using data from Truven Health MarketScan (2009–2015). We selected continuously enrolled patients newly initiating both an SGLT2i and an antifungal between 1 April 2013 and 31 December 2015 within time periods of 30, 60, 90, 180 or 365 days of each other. Adjusted sequence ratios (ASR) were calculated for each time period as the ratio of patients initiating SGLT2i first over those initiating an antifungal first adjusted for time trends in prescribing. Analyses were stratified by sex and type of SGLT2i. Results: There were 23 276 patients who newly initiated both SGLT2i and an antifungal in our study period. These patients were further classified into those initiating the two drugs within 365 ( n = 17 504), 180 ( n = 11 873), 90 ( n = 7697), 60 ( n = 5856) or 30 ( n = 3650) days of each other. Increased risks of mycotic infections were present across all time periods, with the strongest effect observed in the 90‐day interval [ASR 1.53 (confidence interval, CI 1.43–1.60)]. Findings differed by sex [90‐day ASR females: 1.65 (CI 1.56–1.74); males 1.25 (CI 1.14–1.36)] and by SGLT2i [90‐day ASR canagliflozin 1.57 (CI 1.49–1.66); non‐canagliflozin 1.42 (CI 1.31–1.55)]. Conclusion: Initiation of SGLT2i was associated with an increased risk for mycotic infections. Findings from this commercially insured population in the real world are consistent with evidence available from clinical trials.